2017
DOI: 10.1183/13993003.02006-2016
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial inflammation and bacterial load in stable COPD is associated with TLR4 overexpression

Abstract: Toll-like receptors (TLRs) and nucleotide-binding oligomerisation domain (NOD)-like receptors (NLRs) are two major forms of innate immune sensors but their role in the immunopathology of stable chronic obstructive pulmonary disease (COPD) is incompletely studied. Our objective here was to investigate TLR and NLR signalling pathways in the bronchial mucosa in stable COPD.Using immunohistochemistry, the expression levels of TLR2, TLR4, TLR9, NOD1, NOD2, CD14, myeloid differentiation primary response gene 88 (MyD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 42 publications
(55 reference statements)
6
49
2
1
Order By: Relevance
“…The chemokines CXCL9 (Mig), CXCL10 (IP‐10) and CXCL11 (I‐TAC), which all bind to CXCR3 expressed on CD4 + and CD8 + T cells are increased in sputum of patients with COPD and T cells and monocytes show enhanced migration to these chemokines . CD8 + cells in lung express increased bacterial Toll‐like receptors (TLR), indicating that they may be regulated by colonizing bacteria . There is also an increase in innate lymphoid cells, particularly ILC1 and ILC3 cells .…”
Section: Inflammatory Mechanisms In Copdmentioning
confidence: 99%
“…The chemokines CXCL9 (Mig), CXCL10 (IP‐10) and CXCL11 (I‐TAC), which all bind to CXCR3 expressed on CD4 + and CD8 + T cells are increased in sputum of patients with COPD and T cells and monocytes show enhanced migration to these chemokines . CD8 + cells in lung express increased bacterial Toll‐like receptors (TLR), indicating that they may be regulated by colonizing bacteria . There is also an increase in innate lymphoid cells, particularly ILC1 and ILC3 cells .…”
Section: Inflammatory Mechanisms In Copdmentioning
confidence: 99%
“…In COPD, a multitude of bacteria, including potential respiratory pathogens, is often present. In addition, with increasing degrees of airflow limitation, there is also an increased recovery of opportunistic pathogens such as Pseudomonas aeruginosa [46]. This bacterial colonization correlates with the severity of inflammatory response, radiological changes, pathological variations of a local immune response, and increased daily symptoms [47].…”
Section: Microbiota and Copdmentioning
confidence: 99%
“…Reportedly, TLR4 could promote airway neutrophilia in COPD [10], and tagging single nucleotide polymorphisms in TLR4 was related to sputum in ammatory cell induction and lung function decline [11]. A previous study revealed that TLR4 was highly expressed in bronchial mucosa of severe COPD patients compared to health individuals, and its overexpression was positively correlated with CD4+/CD8+ cell in ltration and air ow obstruction [12]. These results suggested TLR4's important role in COPD pathogenesis and progression.…”
Section: Introductionmentioning
confidence: 86%